TOF-Guided Rocuronium Administration Shortens Spontaneous Breathing Recovery and Reduces Consumption Compared to Time-Based Dosing: A Prospective Comparative Study - Ramadhan, Lozan Sagvan; Dr. Haider Nasser Mohammed (Student’s Journal of Health Research Africa, 2026)
Background: Muscle and nerve relaxants, such as rocuronium, are essential in general anesthesia to facilitate endotracheal intubation and achieve optimal relaxation during surgery. However, time-based dosing without objective monitoring often leads to cumulative overdoses, residual neuromuscular blockade, and delayed postoperative respiratory recovery. Quantitative four-pulse response monitoring enables precise dosing but remains underutilized, particularly in resource-constrained settings. This study evaluated the effect of four-pulse response-guided rocuronium administration versus conventional time-based dosing on spontaneous respiratory recovery and total muscle and nerve relaxant consumption during elective surgical procedures. Methods: A prospective, non-randomized comparative clinical study included 150 American Society of Anesthesiologists (ASA) Class I and II adults (aged 16–66 years) undergoing elective surgery at Al-Badari Hospital (Zakho) and Azadi Teaching Hospital (Duhok) between November 2024 and April 2025. Participants were sequentially divided into two groups: Group T (n=75, time-measured doses) and Group S (n=75, ulnar nerve stimulation-measured doses). Ideal body weight (0.6–1.2 mg/kg) was used to initiate rocuronium anesthesia; maintenance doses were either time-measured (Group T) or titrated according to response (Group S). Primary outcome: time from last dose to spontaneous breathing (minutes). Secondary outcome: total rocuronium maintenance dose (mg). Outliers were analyzed using the Mann-Whitney U test and the chi-squared test (SPSS version 23; p-value ≤ 0.05 is statistically significant). Results: The baseline parameters were similar, with small changes in age and height (p=0.021, 0.004). The TOF group’s recovery time was shorter (median (IQR): 20 (10) min vs. 25 (12) min; U=2051.5, p=0.004) and their dosages were lower (6 (7) mg vs. 15 (10) mg; p<0.001). The TOF group had a lower rate of delayed recovery (≥22 minutes) than the other group (35.1% vs. 64.9%; OR=1.875, p<0.001).